Pengembangan Media Pembelajaran Pop-Up Berbasis Sains Kelompok B RA Raden Fatah Podorejo - Wahyuningtyas, Dessy Putri; Nafi’ah, Faizatun (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Learning media development pop-up-based science is a means to help children understand and improve the cognitive ability of children in science. The purpose of this research is: (1) to develop learning science through the media pop-up, (2) to know the application of learning science through the media pop-up, (3) to find out about learning student understanding of science after using the media pop-up. This research uses the methods of research and development (R D ). This study refers to the development of the model of the Dick and Carey. Procedures for developing instructional media pop-up-based science uses several steps, as follows: needs analysis, product design, design and conduct formative evaluation (testing for individuals, the Council groups small, field trial), revision. The results of the validation of the content reaches the level of the validity of the 82%, design validation media reaches 91% and the validity of the classroom teacher reached 90%. This suggests that the learning media worthy and this can be used in the learning process. The cognitive ability of children who use the media pop-up learning increasing, it can be seen from the average percentage value before tests from 61.1 be 88.3. So, by using the pop-up media children understand more about the learning of science